PEMIKIRAN PROF. DR. KASSIM AHMAD DALAM MENGKAJI HADIS - Ernawati Beru Ginting (SHAHIH (Jurnal Ilmu Kewahyuan), 2022)
Kassim Ahmad is an intellectual from Malaysia who doubts the authenticity of the Prophet's hadith. Through his book Hadith: An Initial Assessment, Kassim Ahmad tries to explain his assumptions until he argues that hadith is a form of deviation from the teachings of the Prophet SAW and should not be accepted as a source of Islamic aqidah and sharia. However, he does not necessarily admit that he is a sunnah disbeliever. Kassim Ahmad is known as an anti-hadith who admits that he is Muslim and loves Islam, but does not believe that hadith comes from the Prophet and rejects hadith as a source of Islamic law. But in the end Kassim Ahmad accepted the hadith despite certain limitations.